PENERAPAN MANAJEMEN BERBASIS SEKOLAH MELALUI PENDEKATAN SWOT DI SD NO. 2 WERDI BHUWANA - Chindytia; Ida Bagus Gede Surya Abadi; Ni Kadek Winda Natasya; Putu Yuli Purnasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of School-Based Management (SBM) through the SWOT approach at SD No. 2 Werdi Bhuwana. This research was motivated by the need to evaluate the effectiveness of school management in improving educational quality amid various internal and external challenges. The purpose of this study was to describe the implementation of SBM, identify the internal and external factors influencing its implementation, and formulate school development strategies based on SWOT analysis. This research employed a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, and were analyzed using SWOT analysis to identify strengths, weaknesses, opportunities, and threats related to SBM implementation. The findings indicate that the implementation of SBM at SD No. 2 Werdi Bhuwana achieved a score of 84.01 and was categorized as good. This is reflected in curriculum management based on the Merdeka Curriculum, regular program evaluation, and stakeholder involvement in supporting school activities. The school’s main strengths include competent teachers, strong internal coordination, and a conducive learning environment. However, several challenges remain, such as limited use of learning technology, inadequate supporting facilities, and low parental involvement. Based on the SWOT analysis, school development strategies are directed toward strengthening collaboration with external stakeholders, optimizing the use of learning technology, improving supporting facilities, and enhancing communication with parents to support sustainable educational quality improvement.